Designing speaking activities for a teacher-preparation course: An ESP approach - Leticia Aracelli Salas Serrano (Ma Chung Press, 2018)
Turning a top-down teacher-preparation course into a more meaningful course for teachers involves the identification of the needs of learners. This chapter shows the way a general English course for teachers became an ESP (English for Specific Purposes) course that aimed at meeting the expectations and personal goals of the participants. Teacher-preparation has become an important issue in Mexico as a teacher evaluation process is being carried out along the country as part of recent educational reforms. The results of the needs analysis instrument identified speaking as the most difficult skill for the teachers to master. Based on the participants´ answers, a complement to the original content of the course was created so that participants could reach their own goals in addition to the institutional goals of the preparation. ESP may be an alternative to help learners perform their professional activities in the target language more effectively.